2017
DOI: 10.15761/hpc.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Perception of body image and tendencies of eating behaviour among adolescents

Abstract: Objective: The purpose of this study was to investigate attitude to body image and compare sex and body mass index differences in body perception among schoolchildren of 7-10 grades in Lithuania.Method: Data was obtained from 3248 adolescents (mean age = 14.83 (SD = 1.28), 49.5% male) who fully completed self-report questionnaires. Participants were grouped and subsequently analyzed according to their body mass index and sex. Results:Tendencies among males and females were analyzed. Overall 39.6% of the female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Diet is food that is determined and controlled for a specific purpose. In a layman's sense, adolescents often interpret it as a reduction in food portions to lose weight to achieve an ideal body shape [11], [12] Research by Thompson (2007) that factors that influence body image in individuals are influenced by several factors, namely the influence of body weight and perceptions of fat or thin, culture, life cycle, pregnancy, socialization, self-concept, gender roles and the influence of body image distortion on individual self. This is reinforced by the results of research which shows that most respondents who have a negative body image perception (experiencing dissatisfaction with their body shape) do not only occur in respondents who are overweight (fat and obese) but also respondents with normal nutritional status.…”
Section: Nomentioning
confidence: 99%
“…Diet is food that is determined and controlled for a specific purpose. In a layman's sense, adolescents often interpret it as a reduction in food portions to lose weight to achieve an ideal body shape [11], [12] Research by Thompson (2007) that factors that influence body image in individuals are influenced by several factors, namely the influence of body weight and perceptions of fat or thin, culture, life cycle, pregnancy, socialization, self-concept, gender roles and the influence of body image distortion on individual self. This is reinforced by the results of research which shows that most respondents who have a negative body image perception (experiencing dissatisfaction with their body shape) do not only occur in respondents who are overweight (fat and obese) but also respondents with normal nutritional status.…”
Section: Nomentioning
confidence: 99%
“…Body dissatisfaction and disordered eating appear significant health problems of young people in Lithuania [19][20][21]. Researches in Lithuania show that body image concerns are prevalent in adolescents and students [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Body dissatisfaction and disordered eating appear significant health problems of young people in Lithuania [19][20][21]. Researches in Lithuania show that body image concerns are prevalent in adolescents and students [19,21,22]. A study in the representative sample demonstrated that every second girl of late adolescent age overestimates her body weight, while more than 60% of boys report body weight underestimation [19].…”
Section: Introductionmentioning
confidence: 99%